A pan-cancer perspective analysis reveals the prognostic significance of SLC7A11 in hepatocellular carcinoma - Zhang, Yinxu; Wang, Dai; Chen, Xiaoyang; Wang, Yuxi; Zhang, Guangyu; Liu, Xiaomei (Frontiers in Oncology, 2025)
BackgroundThe cystine/glutamate antiporter SLC7A11 is critically involved in tumorigenesis andferroptosis regulation. However, its comprehensive role in hepatocellular carcinoma (HCC) prognosis and tumor immunity remains elusive.MethodsWe evaluated SLC7A11 expression using immunohistochemistry (IHC) in a clinical HCC cohort and analyzed its prognostic significance. A pan-cancer analysis across The Cancer Genome Atlas (TCGA) datasets was performed to investigate SLC7A11 genetic alterations, its impact on the tumor microenvironment (TME), tumor mutation burden (TMB), and therapy response.ResultsSLC7A11 was significantly upregulated in HCC tissues, and high expression predicted poorer overall survival. Pan-cancer analysis confirmed its aberrant expression and identified a recurrent missense mutation (c.G>A) across various cancers. Elevated SLC7A11 expression correlated with higher TMB and TIDE scores, indicating a potential link to immunosuppression. It was enriched in metabolic pathways and associated with increased M0 macrophage infiltration. Furthermore, SLC7A11 expression positively correlated with response to agents including Gemcitabine and Bortezomib but conferred resistance to Cisplatin and others.ConclusionOur findings establish SLC7A11 as a powerful prognostic biomarker for HCC, unveil its role in shaping an immunosuppressive TME, and highlight its value in predicting response to conventional and emerging therapies, providing a rationale for targeting SLC7A11 in future treatment strategies.